Rehabilitation of Historic Masonry Bridges: Lessons Learned from a Medieval Bridge in Northeast Spain - González Rodrigo, Beatriz; Roig i Olària, Sonia; Fernández-Ordoñez, David; Conde-Salazar Gómez, José María (Revista de la Construcción. Journal of Construction, 2015)
In the Iberian Peninsula there are many masonry bridges enduring over time that require inspection and maintenance. In 2007 it was carried out a restoration project on the bridge of Sant Andreu de Terri (Girona, Spain). Prior to this intervention, the bridge did not meet the safety and comfort requirements for the crossing of people and the walls showed loss of masonry stones and material from joints. The surface was cleaned and replaced the existing metal rail. The board was replaced; waterproof and longitudinal drainage pipes were installed to prevent water infiltration. As result of this action a historical, artistic and architectural heritage construction was recovered re-offering the use for which it was conceived.